1999
DOI: 10.1016/s0741-5214(99)70266-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional status and quality of life after lower extremity revascularization

Abstract: Although the long-term mortality rate is high in the population that undergoes lower limb revascularization, the survivors are likely to retain their limb over time and have good functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 25 publications
(25 reference statements)
3
20
0
3
Order By: Relevance
“…[32][33][34] Responders were more likely to have an intact trial leg and, presumably therefore, to exhibit higher levels of generic but especially disease-specific HRQOL. [35][36][37][38][39][40][41] Like PREVENT III, nonresponse was associated with amputation, and this limited the information available to measure the effects of the alternative management strategies on HRQOL in this patient subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Responders were more likely to have an intact trial leg and, presumably therefore, to exhibit higher levels of generic but especially disease-specific HRQOL. [35][36][37][38][39][40][41] Like PREVENT III, nonresponse was associated with amputation, and this limited the information available to measure the effects of the alternative management strategies on HRQOL in this patient subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Obwohl sich mit der infraingu inalen Bypassanlage bei Diabetikern rein operationstechnisch ähnliche gute Resul tate erzielen lassen wie bei Nichtdiabeti kern [3,43], erreichen die funktionellen Ergebnisse und die Lebensqualität nicht das gleiche Niveau wie bei Patienten oh ne Diabetes [12,14,21,36]. Diabetiker er reichten signifikant schlechtere Werte im SF36 "physical health score" als Nicht diabetiker, und die Wahrscheinlichkeit 4-5 Jahre nach Bypassanlage noch gehfähig zu sein ist für Diabetiker deutlich gerin ger (Odds Ratio 0,2) [21]. Auch das psy chische Wohlbefinden der Nichtdiabeti ker ist nach erfolgreicher Bypassanlage besser als bei den Diabetikern [16].…”
Section: Einfluss Von Diabetes Mellitusunclassified
“…Längsschnitterhebungen zur Lebensqua lität bei Patienten mit CLI sind problema tisch aufgrund der kurzen Lebenserwar tung (5JahresÜberlebensrate 50% [40]), der damit verbundenen hohen Dropout Rate und eines möglichen Selektionsbias zugunsten der weniger schwer erkrankten -mutmaßlich weniger in ihrer Lebens qualität beeinträchtigten -Patienten am [21,33]. Trotz erhaltener Extremität sind je doch die Laufleistungen und Fähigkeiten der CLIPatienten bei der Verrichtung auch nur einfacher Tätigkeiten denen al tersentsprechender Gesunder deutlich un terlegen.…”
Section: Langzeitverlauf Der Lebensqualität Nach Bypasschirurgieunclassified
“…Infrainguinal bypass grafting for limb salvage is major surgery typically performed on patients with multiple comorbidities; undesirable short-and long-term outcomes such as infection, amputation, and death are common [1][2][3][4]. Previously, we found that patients appeared to be willing to undertake remarkable risks for surgery and that their expectations for benefits appeared greater than outcomes suggested by published reports [5].…”
Section: Introductionmentioning
confidence: 99%
“…This work was presented as a poster at the Society for General Internal Medicine Midwest Regional Meeting, Chicago, IL, September 2005 2. To whom correspondence and reprint requests should be addressed at Division of General Surgery, University of Wisconsin, G5/315 CSC, 600 Highland Ave., Madison, WI 53792.…”
mentioning
confidence: 99%